Effects of the Qinghai-Tibet Railway on the Landscape Genetics of the Endangered Przewalski's Gazelle (Procapra przewalskii). Issue 1 (December 2017) - Yu, He; Song, Shiya; Liu, Jiazi; Li, Sheng; Zhang, Lu; Wang, Dajun; Luo, Shu-Jin
Abstract The Przewalski's gazelle (Procapra przewalskii ) is one of the most endangered ungulates in the world, with fewer than 2, 000 individuals surviving in nine habitat fragments on the Qinghai-Tibet Plateau and isolated by human settlements and infrastructure. In particular, the Qinghai-Tibet railway, which crosses the largest part of the gazelle's distribution, remains a major concern because of its potential to intensify landscape genetic differentiation. Here, using mtDNA sequencing and microsatellite genotyping to analyze 275 Przewalski's gazelle samples collected throughout the range, we observed low level of genetic diversity (mtDNA π = 0.0033) and strong phylogeographic structure. Overall, the nine patches of gazelles can be further clustered into five populations, with a strong division between the eastern vs. western side of Qinghai Lake. Our study provides the first evidence of the genetic divergence between the Haergai North and Haergai South gazelle populations, corresponding to the recent construction of a wired enclosure along the Qinghai-Tibet railway less than ten years ago, an equivalent of five generations. Well-designed wildlife corridors across the railway along with long-term monitoring of the anthropogenic effects are therefore recommended to alleviate further habitat fragmentation and loss of genetic diversity in Przewalski's gazelle.